2014
DOI: 10.1007/s10620-014-3258-4
|View full text |Cite
|
Sign up to set email alerts
|

Upper Gastrointestinal Bleeding Caused by Severe Esophagitis: A Unique Clinical Syndrome

Abstract: We have described a unique clinical syndrome in patients with upper gastrointestinal bleeding who have erosive esophagitis. This syndrome is manifest by typical clinical features and is associated with favorable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Upper digestive bleeding was present in 297 (9.88%) of cases with esophagitis. The prevalence is very similar to a study in America, which describes a ratio of 7.85%, with a higher incidence in men [15].…”
Section: Discussionsupporting
confidence: 87%
“…Upper digestive bleeding was present in 297 (9.88%) of cases with esophagitis. The prevalence is very similar to a study in America, which describes a ratio of 7.85%, with a higher incidence in men [15].…”
Section: Discussionsupporting
confidence: 87%
“…Alcohol decreases the lower esophageal sphincter tone and inhibits peristalsis of the esophagus, resulting in an increase and prolongation of gastroesophageal reflux [10]. A study on GI bleeding caused by esophagitis demonstrated lower mortality and rebleeding rate in patients with esophagitis versus other bleeding etiology; however, the effect of alcohol use was not investigated [21]. In contrast, another study of 213 patients with mortality from gastroesophageal reflux disease showed that alcohol abuse increased the risk of death from hemorrhagic esophagitis, which was the cause of death in many (n = 82) of the study patients [22].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with UGIB secondary to esophagitis, hematemesis is more common than melena. 7 The presence of associated odynophagia and dysphagia will depend on the chronicity and severity of the underlying condition.…”
Section: Esophagitismentioning
confidence: 99%